Classical Cesarean Section - Kan, Amano (The Surgery Journal, 2020)
Cesarean section is the most common surgery in obstetrics. Several techniques are proposed according to the indication and the degree of urgency. Usually laparotomy followed by hysterotomy with a low transverse incision is preferable. However, in cases in which it is difficult to access the lower uterine segment, such as that in preterm labor, dense adhesion, placenta previa/accrete a vertical hysterotomy (classical cesarean section) may be needed. Although a smooth and gentle delivery of the fetus is possible through the vertical incision, uterine closure is technically difficult. To decrease the risks of hemorrhage and adhesion, a speedy and skillful technique is mandatory. The most serious risk of vertical incision in the contractile corpus is uterine rupture in the subsequent pregnancy. Therefore, cases of prior classical cesarean section are contraindicated for trial of labor after cesarean section.
Keywords: cesarean section; vertical uterine incision; classical cesarean section; uterine rupture